Unravelling copper effect on the production of varietal thiols during Colombard and Gros Manseng grape juices fermentation by Saccharomyces cerevisiae - Dournes, Gabriel; Dufourcq, Thierry; Suc, Lucas; Roland, Aurélie; Mouret, Jean-Roch (Frontiers in Microbiology, 2023)
Nowadays the rapidly increasing organic vineyard management with the utilization of copper as sole fungal control pesticide against downy mildew raises once again the question of copper impact on varietal thiols in wine. For this purpose, Colombard and Gros Manseng grape juices were fermented under different copper levels (from 0.2 to 3.88 mg/L) to mimic the consequences in must of organic practices. The consumption of thiol precursors and the release of varietal thiols (both free and oxidized forms of 3-sulfanylhexanol and 3-sulfanylhexyl acetate) were monitored by LC-MS/MS. It was found that the highest copper level (3.6 and 3.88 mg/L for Colombard and Gros Manseng respectively) significantly increased yeast consumption of precursors (by 9.0 and 7.6 % for Colombard and Gros Manseng respectively) . For both grape varieties, free thiol content in wine significantly decreased (by 84 and 47 % for Colombard and Gros Manseng respectively) with the increase of copper in the starting must as already described in the literature. However, the total thiol content produced throughout fermentation was constant regardless of copper conditions for the Colombard must, meaning that the effect of copper was only oxidative for this variety. Meanwhile, in Gros Manseng fermentation, the total thiol content increased along with copper content, resulting in an increase up to 90 %; this suggests that copper may modify the regulation of the production pathways of varietal thiols, also underlining the key role of oxidation. These results complement our knowledge on copper effect during thiol-oriented fermentation and the importance of considering the total thiol production (reduced+oxidized) to better understand the effect of studied parameters and differenciate chemical from biological effects.